Penerapan Algoritma K-Means Clustering dalam Penentuan Nilai Huruf pada Permainan Susun Kata Bahasa Bali - I Made Rian Yuliawan; Duman Care Khrisne; Putu Arya Mertasana (Jurnal SPEKTRUM, 2019)
Word stacking is a very popular game in the world. In general word stacking games are called Scrabble games. Word stacking games are educational games that prioritize vocabulary. There are several important aspects in word stacking games, including the configuration of the reference word and the value of letters. However, until now, there are no word stacking games with game configurations that use Balinese as a language reference. The purpose of this study is to design a word stacking game in Balinese as a language reference and determine the value of each letter used in the word. In its design, the word used is sourced from the Second Edition of the Balinese Dictionary which consists of 10441 words. All the words will be grouped by the value using the K-Means Clustering method. Before all the words grouped with K-Means Clustering the words will be determined the frequency of occurrence of each letter in the word, appearance at the beginning and end of the word, and the frequency of the use of letters as a prefix and suffix. The results obtained from grouping with K-Means Clustering are letters A having the smallest value, namely 1 point and letters C, J, W, and Y have the largest value, 10 points.